Impact of Non-cardiac Comorbidities on Long-Term Clinical Outcomes and Health Status After Acute Heart Failure in China - Huo, Xiqian; Zhang, Lihua; Bai, Xueke; He, Guangda; Li, Jiaying; Miao, Fengyu; Lu, Jiapeng; Liu, Jiamin; Zheng, Xin; Li, Jing (Frontiers in Cardiovascular Medicine, 2022)
Background: Individual non-cardiac comorbidities are prevalent in HF, however, few studies reported how the overall burden of non-cardiac comorbidities impacts long-term outcomes, and it is unknown whether this burden is associated with the change in health status. Aims: To assess the association of the overall burden of non-cardiac comorbidities with clinical outcomes and quality of life (QoL) in patients hospitalized for heart failure (HF). Methods: We prospectively enrolled patients hospitalized for HF from 52 hospitals in China. Eight key non-cardiac comorbidities (diabetes, chronic kidney disease, chronic obstructive pulmonary disease, anemia, stroke, cancer, peripheral arterial disease, liver cirrhosis) were included and patients were categorized into four groups: none, one, two, and three or more comorbidities. We fitted Cox proportional hazards models to assess the burden of comorbidities on 1-year death and rehospitalization. Results: Among 4866 patients, 25.3% had none non-cardiac comorbidity, 32.2% had one, 22.9% two, and 19.6% three or more in China. Compared with those without non-cardiac comorbidities, patients with three or more comorbidities had higher risks of 1-year all-cause death (HR 1.89; 95%CI 1.48-2.39) and all-rehospitalization (HR 1.35; 95%CI 1.15-1.58) after adjustment. Although patients with HF all experienced longitudinal improvement in QoL over 180 days after discharge, those with three or more non-cardiac comorbidities had an unadjusted 11.4 (95%CI -13.4 to -9.4) lower Kansas City Cardiomyopathy Questionnaire (KCCQ) scores than patients without comorbidities, and the difference decreased to -6.4 (95%CI -8.6 to -4.2) after adjustment for covariates. Conclusion: Among patients hospitalized with HF in this study, higher burden of non-cardiac comorbidities were significantly associated with worse health-related quality of life, and increased risks of death, rehospitalization post-discharge. The findings underscore the need to adequately address comorbidities management in standardized HF care.